Anti-PD-1 Vasculitis of the central nervous system or radionecrosis?. Issue 1 (19th December 2017) - Sun, Roger; Danlos, Francois-Xavier; Ammari, Samy; Louvel, Guillaume; Dhermain, Frédéric; Champiat, Stéphane; Lambotte, Olivier; Deutsch, Eric
Abstract : Commentary on « Cerebral vasculitis mimicking intracranial metastatic progression of lung cancer during PD-1 blockade » by Läubli H et al., J Immunother Cancer. 2017;5:46. The authors diagnosed a cerebral tumor-like lymphocytic vasculitis associated with anti-endothelial cell auto-antibodies secondary to anti-PD-1 therapy, treated by surgical resection and corticosteroids. We thought that this diagnosis should be discussed for at least two reasons. First, etiological explorations were not sufficient. Second, the diagnostic of radionecrosis should also be discussed.